Bakery products science and technology - Zhou, Weibiao; Hui, Y. H. (Yiu H.) (Chichester, West Sussex, UK : John Wiley & Sons Inc., 2014)
Baking is a process that has been practiced for centuries, and bakery products range in complexity from the simple ingredients of a plain pastry to the numerous components of a cake. While currently there are many books available aimed at food service operators, culinary art instruction and consumers, relatively few professional publications exist that cover the science and technology of baking. In this book, professionals from industry, government and academia contribute their perspectives on the state of industrial baking today. The second edition of this successful and comprehensiv.
Aspects in formulating chemical leavenersLeavening agents; Acidulants and acids; Role of leavening agents; References; 10 Ascorbic Acid and Redox Agents in Bakery Systems; Introduction; Basics of dough development; Redox requirements in different bread making processes; Ascorbic acid; Oxygen; Azodicarbonamide; Potassium bromate; l -Cysteine hydrochloride; Sodium metabisulfite; Sulfhydral oxidase; Glucose oxidase; Transglutaminase (TG); Future outlook; References; 11 Sugar and Sweeteners; Overview; Sugar; The perfect substitute; Alternative sweeteners; References.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Baking; Baked product; Baked products; Baking; COOKING -- General; Baked products; Baking; Electronic books